2019
DOI: 10.5194/nhess-2019-96
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental controls on surf zone injuries on high-energy beaches

Abstract: Abstract. The two primary causes of surf zone injuries (SZIs) worldwide, including fatal drowning and severe spinal injuries, are rip currents (rips) and shore-break waves. SZIs also result from surfing and body boarding activity. In this paper we address the primary environmental controls on SZIs along the high-energy meso-macrotidal surf beach coast of SW France. A total of 2523 SZIs recorded by lifeguards over 186 sample days during the summers of 2007, 2009 and 2015 were combined with measured and/or hindc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Alignment of climatic and economic conditions may be related to the increased fatal drowning numbers in Guanacaste and Puntarenas in those years (Fig. 3c), consistent with observations by Castelle et al (2019), in which drowning was more likely to occur on warm sunny days due to increased number of beachgoers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Alignment of climatic and economic conditions may be related to the increased fatal drowning numbers in Guanacaste and Puntarenas in those years (Fig. 3c), consistent with observations by Castelle et al (2019), in which drowning was more likely to occur on warm sunny days due to increased number of beachgoers.…”
Section: Discussionsupporting
confidence: 87%
“…Meteorological conditions also affect the number of beachgoers, who in general prefer sunnier and hotter days (Castelle et al 2019). On the Costa Rican Pacific Coast, these conditions are exacerbated during the onset of the warmer phase of El Niño-Southern Oscillation (ENSO; Instituto Meteorológico Nacional 2020) causing a reduction in rainfall and frequency, and an increase in ambient temperatures along Puntarenas and Guanacaste (Wayle et al 1996;Waylen and Sadí, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificdata www.nature.com/scientificdata/ improve a range of state-of-the art shoreline change models from the time scale of hours to decades 2,21,44,45 , to validate remotely-sensed shoreline estimation from publicly available satellite images 46 , to identify the morphological controls on spine injuries and drowning on surf beaches 47,48 , and to address the uncertainties in past and future multi-decadal shoreline evolutions 49,50 . In addition, a couple of intensive field experiments have been performed at Truc Vert beach 51 .…”
Section: Background and Summarymentioning
confidence: 99%
“… 42 Here, the life-risk was found to systematically increase with the wave factor Wf , which is in line with Castelle et al , but contrast with Scott et al 43 in UK where hazard was maximised for just below average Wf . In a previous study, 44 it was qualitatively shown that the beach morphology, which has a profound impact on rip current hazard, was important to the number of drowning incidents. Given the low number of studied seasons and events, and the likely contrasting beachgoer profiles between seasons, it was not possible to robustly address the influence of the bathymetry.…”
Section: Discussionmentioning
confidence: 94%
“…Our models tend to overestimate the risk on days associated with moderate to high risks; some variables may thus be unknown, related to the beach morphology and the beach attendance. First, the summer beach morphology along the Gironde coast is very variable with rip channel exhibiting different morphologies from one summer to another, 44 and even in space with more gently sloping and less channelized beaches northwards. Given that, for instance, the relative depth of the rip channels is critical to rip current flow speed, 46 and thus physical hazard, and that beach type also influence attendance 47 consideration of a constant beach morphology is limiting.…”
Section: Discussionmentioning
confidence: 99%